2020
DOI: 10.1038/s41592-020-0816-x
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional nanoscopy of whole cells and tissues with in situ point spread function retrieval

Abstract: Single-molecule localization microscopy is a powerful tool for visualizing subcellular structures, interactions, and protein functions in biological research. However, inhomogeneous refractive indices inside cells and tissues distort the fluorescent signal emitted from single-molecule probes, which rapidly deteriorates resolution with increasing depth. We propose a method that enables the construction of an in situ 3D response of single emitters directly from single-molecule blinking dat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 47 publications
1
66
0
Order By: Relevance
“…In principle, they can directly estimate the proximity of biomoleculs by fluorescence colocalization without biochemical recognition reactions such as DNA proximity. However, this resolution can vary considerably in optically complex samples, and the z -axis resolution is still limited 53 . Furthermore, registration errors from sample drift especially in multichannel imaging often lead to incorrect colocalization analysis 54 .…”
Section: Discussionmentioning
confidence: 99%
“…In principle, they can directly estimate the proximity of biomoleculs by fluorescence colocalization without biochemical recognition reactions such as DNA proximity. However, this resolution can vary considerably in optically complex samples, and the z -axis resolution is still limited 53 . Furthermore, registration errors from sample drift especially in multichannel imaging often lead to incorrect colocalization analysis 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Methods have been described to retrieve the PSF in situ and should be considered. 160 In any case, disagreement between theoretical and experimental PSFs cause poor fitting results in e.g. PSF localization, which deteriorates the quality of the reconstruction.…”
Section: Perspectives On Methods and Applicationsmentioning
confidence: 99%
“…With similar intentions to achieve high localization precision, Xu et al presented a different approach called in situ point spread function retrieval (INSPR) SMLM. 73 The system showed the ability to construct an in situ 3D response of single emitters directly from single-molecule blinking data sets. The authors demonstrated the use of this method in imaging various organelles in mammalian cells (e.g., mitochondrial networks and nuclear pores) as well as in tissue (e.g., amyloid-β plaques and dendrites in brain tissues) at a depth of <20 μm, achieving 7–12 nm lateral and 21–45 nm axial precision in localization.…”
Section: Super-resolution Microscopy For Imaging Of Single Cells Andmentioning
confidence: 99%